Pelaksanaan Lelang Terhadap Barang Rampasan - Ralia Fitria; Elizabeth Siregar; Erwin Erwin (Fakultas Hukum, Universitas Jambi, 2022)
The purpose of this study was to determine the feasibility procedure for the auction of the booty carried out by the Jambi District Attorney and to find out the obstacles in the implementation of the booty auction and the efforts to overcome it. The results of the research are: The execution process of the looted goods carried out by the Jambi District Attorney is carried out in 3 (three) stages, namely: 1) Pre Auction, namely before the sale of the booty auction, it is necessary to obtain a permit. 2) The implementation of the auction as well as the auction of the confiscated goods can be carried out and does not conflict with the applicable laws and regulations. 3) After the auction, as must be done steps to deposit and report the results of the auction and make minutes of the meeting. The obstacle that often occurs in the execution of the AGO's execution auction is the issuance of a permit for the auction of looted goods carried out by the Indonesian Attorney General's Office which needs consideration. Efforts that can be made in dealing with the problem of the length of time for issuing permits to conduct auctions and determining the limit price of confiscated goods require quick and decisive action from the Attorney General's Office of the Republic of Indonesia. ABSTRAK Â Tujuan penelitian ini adalah untuk mengetahui Â prosedur kelayakan pelaksanaan pelelangan barang rampasan yang dilakukan oleh Kejaksaan Negeri Jambi dan untuk mengetahui kendala dalam pelaksanaan pelelangan barang rampasan tersebut dan upaya untuk mengatasinya. Hasil penelitian adalah: Proses eksekusi terhadap barang rampasan yang dilakukan oleh Kejaksaan Negeri Jambi dilakukan dengan 3 (tiga) tahap, yaitu: 1)Pra Lelang yaitu sebelum dijual lelang barang rampasan perlu mendapatkan izin. 2)Pelaksanaan Lelang sebagaimana pelaksanaan lelang terhadap barang rampasan tersebut dapat dilaksanakan dan tidak bertentangan dengan peraturan perundang-undangan yang berlaku. 3)Pasca Lelang sebagaimana harus dilakukan langkah penyetoran dan laporan hasil lelang dan membuat risalah rapat. Kendala yang sering terjadi dalam pelaksanaan lelang eksekusi Kejaksaan adalah pengeluaran surat izin lelang barang rampasan yang dilakukan oleh Kejaksaan Agung RI yang perlu pertimbangan. Upaya yang dapat dilakukan dalam menangani masalah lamanya waktu pengeluaran izin pelaksanaan lelang dan penentuan harga limit barang rampasan perlu adanya tindakan yang cepat dan tegas dari Kejaksaan Agung Republik Indonesia.